Development of a Picture Book to Enhance Children’s Understanding of Flood Disaster Mitigation: Group B2, Al-Hikmah Rusa Kencana Kindergarten, Toili Subdistrict, Luwuk Banggai Regency - Novita Ayu Kristyaningrum; Fitriana Fitriana; Sita Awalunisah; Andi Agusniatih (Journal of Educational Sciences, 2026)
Early childhood education plays a crucial role in fostering children’s preparedness for disaster risks, particularly floods, which frequently occur in Toili Subdistrict, Banggai Regency. This study aims to develop a picture storybook as a learning medium to enhance children’s understanding of flood disaster mitigation at Al-Hikmah Rusa Kencana Kindergarten. The study employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 10 children in Group B2. Data collection techniques included observation, interviews, documentation, and expert validation sheets, while data analysis utilized both qualitative and quantitative methods through validity tests and t-tests. The results indicated that the picture book “Raka the Water Hero” received an expert validation score of 87.5% for both content and media, categorized as highly valid. The pilot test results showed an increase in children’s understanding of flood disaster mitigation, as evidenced by an increase in the average pre-test score from 7.5% to 92.5% on the post-test, as well as a t-calculated value greater than the t-table value at a 5% significance level. Thus, the picture book is effective as a learning medium for improving young children’s understanding of flood disaster mitigation.